2021
DOI: 10.1515/dmpt-2021-0126
|View full text |Cite
|
Sign up to set email alerts
|

Virgin coconut oil abrogates depression-associated cognitive deficits by modulating hippocampal antioxidant balance, GABAergic and glutamatergic receptors in mice

Abstract: Objectives GABA and glutamate neurotransmission play critical roles in both the neurobiology of depression and cognition; and Virgin coconut oil (VCO) is reported to support brain health. The present study investigated the effect of VCO on depression-associated cognitive deficits in mice. Methods Thirty male mice divided into five groups were either exposed to chronic unpredicted mild stress (CUMS) protocol for 28 days or pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…These generated free radicals and ROS undergo oxidative reactions with lipids such as the long chain polyunsaturated fatty acids of the eye and play a role in the pathogenesis of most ocular diseases (Nagakannan et al 2012; Njie-Mbye et al 2013). Sleep deprivation is globally known to induce oxidative stress (Li et al 2018a), as well as a driver of lipid peroxidation evident in unusually elevated levels of the oxidant metabolite, MDA (Edem et al 2021). In this study, ocular lipid peroxidation with increased ocular MDA levels following SD was observed, however it was ameliorated following tramadol intervention ameliorated sleep deprivation-induced sleep lipid peroxidation.…”
Section: Discussionmentioning
confidence: 54%
“…These generated free radicals and ROS undergo oxidative reactions with lipids such as the long chain polyunsaturated fatty acids of the eye and play a role in the pathogenesis of most ocular diseases (Nagakannan et al 2012; Njie-Mbye et al 2013). Sleep deprivation is globally known to induce oxidative stress (Li et al 2018a), as well as a driver of lipid peroxidation evident in unusually elevated levels of the oxidant metabolite, MDA (Edem et al 2021). In this study, ocular lipid peroxidation with increased ocular MDA levels following SD was observed, however it was ameliorated following tramadol intervention ameliorated sleep deprivation-induced sleep lipid peroxidation.…”
Section: Discussionmentioning
confidence: 54%
“…The NOR test, a test for determining changes in non-spatial working memory, was performed as previously reported [35] . The animals had a first trial (T1) experience in which they were kept in a white, opaque test room with two identical items for three minutes, after which an inter-trial time (IT) of thirty minutes was noted.…”
Section: Methodsmentioning
confidence: 99%
“…To calculate the percentage of correct modifications, the frequencies of the correct alterations (ABC, ACB, BCA, BAC, CBA, or CAB) between the arms were noted. Edem et al, ($year$) [35] , and calculated using the formula below. The calculation for the percentage alternation is provided below: …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations